Komponen Kurikulum Pendidikan Agama Islam (PAI) (Antara Teori dan Praktek) - Nanang Budianto (STAIFAS-Press, 2018)
The role of the education curriculum in terms of any aspect is very urgent. This is related to the process of scientific transformation from the older generation to the younger generation. It is fitting for the curriculum to be evaluated to be able to adjust to the demands of the times that continue to go into the era of progress both scientifically and the creativity of various thoughts that often clash with religious values. The curriculum component must consist of at least four components, namely goals, materials, methods, and evaluations. Another thing that must be considered again is that from year to year the curriculum will continue to change according to changes and developments in human thought. But how to overcome these changes, this is very dependent on the accuracy of the curriculum developer itself. One thing that must and must be considered is how Islamic education institutions can anticipate this problem, without forgetting the essence of the teachings of Islam itself. Keyword: Basic Concepts, Components and Curriculum Philosophy